Th1/Th2 cytokine production by clove-treated mice - Bachiega, Tatiana Fernanda [UNESP]; Orsatti, Claudio Lera [UNESP]; Pagliarone, Ana Carolina [UNESP]; Missima, Fabiane [UNESP]; Barreto Sousa, Joao Paulo; Bastos, Jairo Kenupp; Sforcin, Jose Mauricio [UNESP] (Taylor & Francis Ltd, 2009)
Although clove possesses several biological and therapeutic properties, its immunomodulatory action has not been fully investigated. The goal of this work was to investigate the effect of administration of the water extract of clove over a short-term to BALB/c mice on Th1 (IFN-gamma and IL-2) and Th2 (IL-4 and IL-10) cytokine production. After treatment, spleen cells were aseptically removed and cells were stimulated with concanavalin A. Supernatants of cell cultures were used for cytokine determination by ELISA. The chemical composition of the extract was also carried out, revealing that eugenol(4-allyl-2-methoxyphenol) was the major component in our sample. Although the anti-inflammatory action of clove has been mentioned, our data showed that clove administration to mice did not influence the Th1/Th2 cytokine balance. Further studies dealing with cytokine expression and production will provide a better understanding of clove's immunomodulatory and anti-inflammatory actions, using different extract concentrations and different intake periods.
Keywords: clove; cytokines; spleen cells; immunomodulation